Animal manure application effects on soil properties and okra ( Abelmoschus esculentus L) growth and yield performance - Benedict O Unagwu; Roseline U Ayogu (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Increase in global population and food demands have necessitated the need to enhance the health status of agricultural soils to overcome retrogresses in crop yields. Thus, amply use of animal manures is critical to improving low fertility status that characterised most agricultural soils in the tropics.Method This study investigated the effects of various animal manure types on soil properties and performance of okra (Abelmoschus esculentus L) grown on a degraded coarse-textured ultisol. The treatments were: T1, poultry manure; T2, cow manure; T3, pig manure applied at 702 g pot-1 (equivalent to 30 t ha-1) to a 10 kg potted soil and T4, control unamended soil.Results Amended treatments had 0.73-10.9% increase in organic matter, 191-370% increase in soil N, 30.4-170% and 25.5-76.5% increase in soil P and K, respectively relative to the control treatment. Amended treatments recorded significantly higher (p <0.05) plant height, stem girth, okra biomass and yields compared with the control treatment. Poultry manure showed superiority over cow manure and pig manure for pH, soil nutrients, okra yield, okra growth and yield parameters measured.Conclusion The results indicate that animal manure application increased okra yield and enhanced the fertility status of a degraded coarse-textured ultisol. Thus, application of animal manures can help overcome low fertility challenges associated with degraded tropical soils.